CircDDX17 inhibits invasive progression of pituitary adenomas by sponging miR-1279 and regulating CADM2 expression - Yue, Xiao; Lan, Fengming; Liu, Weiping (Frontiers in Oncology, 2023)
Increasing evidence has revealed that circDDX17 plays significant regulatory roles in tumor progression. In the present study, we investigated the role of circDDX17 in pituitary adenomas (PA).Methods: RT-qPCR was performed to detect the expression of circDDX17, miR-1279 and CADM2 in PA tissues. Cell abilities of migration and invasion were examined by wound healing and transwell assays. Dual-luciferase reporter, RIP and RNA pull-down assays were applied to confirm the associations among circDDX17, miR-1279 and CADM2. Xenograft tumor experiments were performed to investigate the roles of circDDX17 in vivo.In the present study, we found that circDDX17 was down-regulated in PA tissues correlated with invasion, tumor size and PA patients' progression free survival. Enforced-expression of circDDX17 significantly inhibited migration and invasion through miR-1279. Notably, CADM2 was verified as the direct binding target of miR-1279 and silencing the expression of CADM2 reverses the tumor suppressing effects induced by circDDX17 overexpression. We demonstrated that circDDX17 up-regulated the expression of CADM2 by sponging miR-1279, which suppressed the invasive biological behaviors of PA.CircDDX17 may serve as a tumor suppressor and potential promising biomarker and effectively therapeutic target for the management of PA.